Investigate The Process And Problems Of Teacher Education Process Faculty In The Rajabhat University In Northeast - ศรีเมือง ธนวรรณพร; สมะวรรธนะ รองศาสตราจารย์ดร.กนก; หัตถพรหม ประยงค์ (Journal for Developing the Social and Community, 2015)
The purposes of this research were: to investigate the process and problems of teacher education process Faculty in the Rajabhat University in Northeast. The population of this study consists of 12 Deans and 76 Chairman of the departments. The structured interview data forms were used with the deans and the questionnaires were used with the chairman of the departments in Faculty of Education in the Rajabhat University in Northeast. The data were analyzed in terms of percentages, arithmetic means and standard deviations. Faculty of Education in the Rajabhat University in Northeast in accordance with the four steps of staff development system as follows: Firstly Diagnosing Development Needs, the policy, objectives, and essentials of staff development were established by studying, collecting and analyzing data. Secondly: Design of Development Plans, the goals and objectives, procedures and budget of staff development were assigned. Five years plan was established, and the purpose of staff development mostly concerning with transmission of knowledge, and the unitizing of the new technology. Thirdly: Implementing Development Program, the technique employed in the development program were group and individual techniques. Finally: Evaluation the Development Program, reporting results of evaluation were used for improvement of the work and the new project. The results of the questionnaires responses by the Chairman of the departments according to the 4 phases of staff development revealed that the diagnostic phase was perform at the high level, the others were at the low level. Problems in staff development were found as follows: in sufficiency of budget for operation, lacking of staff participation in planning process, deficiency of experts involving in planning, and in evaluation of staff development process couldn’t demonstrated the achievement of the goals. The problems in all phases were at low level.